Media Pembelajaran “Film” Berbasis ICT Dalam Pembelajaran Istima’ Kelas VII MTs Hidayatul Ummah Balongpanggang - Khoirur, Riziki (Ngaliman: Jurnal Pengabdian Kepada Masyarakat, 2025)
Arabic is a language that is still less popular with students compared to English because many consider it to be a complicated and difficult science to learn. In order to learn Arabic more easily, it is necessary to use methods and utilize learning media, especially technology-based ones because the increasingly rapid development of technology in the current era of globalization cannot be avoided, and its impact on the world of education is very significant. This research aims to explain: the application of film media with the help of information and communication technology tools and the background to its selection in learning istima' skills as well as supporting and inhibiting factors in its application. This study used qualitative research methods. This research was conducted at MTs Hidayatul Ummah Balongpanggang. Data collection was carried out using interviews, observation and documentation methods. The results obtained in this research show that: 1) The use of film media in ICT-based istima' learning carried out by teachers for grade 7 students at MTs Hidayatul Ummah Balongpanggang is very good. And the result for their own listening skills is that students understand what is taught by the teacher and student activity increases and the teacher holds daily exams which are carried out twice in 1 semester. 2) Factors that support the use of film media in ICT-based istima' learning for grade 7 students at MTs Hidayatul Ummah Balongpanggang are the availability of facilities to use the media. audio-visual film as a learning medium. Meanwhile, the inhibiting factor is that not all material can be presented in media form.